Binding of organophosphate insecticides with serum albumin: multispectroscopic and molecular modelling investigations. (4th March 2017) - Suganthi, M.; Elango, Kuppanagounder P.
ABSTRACT: The interaction between two organophosphate insecticides (monocrotophos and phosphamidon) and bovine serum albumin (BSA) under physiological conditions is investigated by UV-Vis, fluorescence (steady state, synchronous and three-dimensional) and circular dichroism spectroscopy. The UV-Vis and fluorescence spectral studies indicate the formation of complex between BSA and the insecticides. The complex formation is a spontaneous process as evidenced by negative free energy changes. The positive values of entropy changes reveal that hydrophobic forces played the major role in the interaction process, which is well supported by the molecular docking studies. Synchronous and three-dimensional fluorescence investigations suggest that there is no significant change in the conformation of BSA upon binding with the insecticides, which is strongly supported by the results of circular dichroism spectral studies.